The real real thing the model in the mirror of art - Steiner, Wendy 1949- (Chicago University of Chicago Press, 2010)
In this view of contemporary culture, Wendy Steiner shows us the arts in the process of a wholesale reorintation. She shows the arts searching out a new ethical stance through the model figure: by stressing the model's identity as a real person beyond the artwork, they acknowledge the audience's independent existence, too, unpredictable and constitutive of artistic meaning. In the process, the arts are redefined as real-world interactions exploring the promise of empathy, reciprocity, and egalitarian connection.-- Publisher.
What is a model? -- Yesterday's models : stories of the creation of women -- I'm not being there : artist, model, celebrity -- What happens to art when virtually everything is virtual? -- "Ecstatic cahoots" : new hierarchies in contemporary art -- Mother, father, mirror : art that remodels the world -- The latest models : collaborative creation stories -- On garde : avant or derri·ere -- The aesthetic gift : Hawthorne, bioethics, Hairspray.
Includes bibliographical references and index.
Keywords: Artists and models in art; Artists' models in literature; Artists' models; Arts, Modern -- 20th century -- Themes, motives; Arts, Modern -- 21st century -- Themes, motives